Microphysical controls on the isotopic composition of wintertime orographic precipitation. Issue 12 (29th June 2016) - Moore, M.; Blossey, P. N.; Muhlbauer, A.; Kuang, Z.
Abstract: The sensitivity of mixed‐phase orographic clouds, precipitation, and their isotopic content to changes in dynamics, thermodynamics, and microphysics is explored in idealized two‐dimensional flow over a mountain barrier. These simulations use the Weather Research and Forecasting (WRF) model with stable water isotopologues (HDO and H 2 18 O), which have been integrated into the Thompson microphysics scheme within WRF as part of the present project. In order to understand how the isotopic composition of precipitation ( δ 18 O precip ) is fixed, the mountain height, temperature, and the prescribed cloud droplet number concentration (CDNC) have been varied in a series of simulations. For the given range of values explored in this work, changes in mountain height and temperature induce stronger responses in domain‐averaged δ 18 O precip than do changes in CDNC by a factor of approximately 10. The strongest response to changing CDNC leads to local variations of δ 18 O precip of about 3‰, though those occur in regions of weak precipitation (<0.1 mm h −1 ). Changes in δ 18 O precip can be understood through the microphysical pathways by which precipitable hydrometeors are formed and by the isotopic signature associated with each pathway. The decrease in δ 18 O precip with increasing mountain height is not just a function of decreasing temperature but also reflects the changing contributions and distinct isotopic signatures of riming of cloud liquid and vapor deposition onto snow, the leading sources of precipitation in these simulations. The changes in δ 18 O precip with mountain height, temperature, and CDNC are governed in part by the microphysical pathways through which precipitating hydrometeors are formed and grow. Key Points: Distinct isotopic signatures of microphysical processes can be determined Temperature and mountain height control precipitation isotopic composition more strongly than CDNC Microphysical changes with CDNC, temperature, and mountain height establish isotopic composition